Plan de mejoramiento para la producción del café de la asociación agroartesanal de productores de café de altura Puyango PROCAP - Apolo Espinoza, José Hernesto (2015)
This research project called "Improvement Plan for the Production of Coffee Growers Association Agroartesanal Café de Altura Puyango" PROCAP "was held in the parish Alamor, Puyango Canton, site where farms of producers that they are found part of this Association. The main objective of this work is to propose an improvement plan for the PROCAP Organization, which contribute to improving the production and coffee prices. The methodology consisted of making a diagnosis using SWOT analysis such as the current situation of coffee farms, and marketing processes; for deffinir strategies, projects and activities aimed at improving the partnership. The results indicate that planning in the coffee plantations is inefficient. It has not been done renovation of coffee plantations. Lack of financial administrative staff working permanently. Lack of technical assistance in administrative matters. Absence of a working capital account for collection of the product. Shortage of irrigation systems to ensure the harvest. Low productivity per hectare. High production costs. Limited control of crop pests and diseases. Lack of a plan for the coffee farm composting. The plantation management is traditional so do not record the activities on the farm. The improvement plan proposed hiring an agricultural technician and finance permanently. Formulation of a training program in the administrative field for members of PROCAP, creating a savings and credit, coffee improvement project, establishment of an agreement with the MAGAP, design records for the coffee production process, organization to carry out visits to other productive sectors of the country and abroad. PROCAP is concluded that the Association has the capacity to overcome the weaknesses found for the proper operation thereof and to the welfare of their partners / ace. Therefore it is recommended to implement the plan and the activities proposed in this paper so that they can leverage their strengths and opportunities linked to the production and marketing of coffee.